1995
DOI: 10.1074/jbc.270.44.26570
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Sequences Which Regulate the Expression of Drosophila melanogaster Doc Elements

Abstract: Doc is one of 50 or more mobile DNA elements that have been identified in the fruit fly Drosophila melanogaster . Doc elements lack terminal repeats, instead terminating at the 3Ј end in runs of adenine residues flanked by polyadenylation signals. They differ in size, being variously truncated at the 5Ј end, and are flanked by target site duplications which vary in length from 10 to 14 bp 1 (Schneuwly et al., 1987;Driver et al., 1989). Complete family members are ϳ4.7 kb in length and potentially encode a puta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 52 publications
(75 reference statements)
0
18
0
Order By: Relevance
“…Such downstream promoter sequences have been found in TATA-containing promoters (see, e.g., Lewis and Manley 1985;Nakatani et al 1990; Lee et al 1992;Emanuel and Gilmour 1993;Purnell and Gilmour 1993), as well as in TATA-less promoters (see, e.g., Biggin and Tjian 1988;Perkins et al 1988;Soeller et al 1988;Smale and Baltimore 1989;Jarrell and Meselson 1991;Contursi et al 1995;Minchiotti et al 1997). It appears that many of these downstream promoter sequences are involved in basal transcription, but it is also important to consider that some downstream promoter sequences might be binding sites for sequence-specific transcriptional activators.…”
mentioning
confidence: 99%
“…Such downstream promoter sequences have been found in TATA-containing promoters (see, e.g., Lewis and Manley 1985;Nakatani et al 1990; Lee et al 1992;Emanuel and Gilmour 1993;Purnell and Gilmour 1993), as well as in TATA-less promoters (see, e.g., Biggin and Tjian 1988;Perkins et al 1988;Soeller et al 1988;Smale and Baltimore 1989;Jarrell and Meselson 1991;Contursi et al 1995;Minchiotti et al 1997). It appears that many of these downstream promoter sequences are involved in basal transcription, but it is also important to consider that some downstream promoter sequences might be binding sites for sequence-specific transcriptional activators.…”
mentioning
confidence: 99%
“…2). Functional interactions between DPE and Inrs located at a specific distance are widely documented (12)(13)(14)(15)(16). The finding that DE1 mimics DPE in the activation of the same Inr is novel, and adds knowledge on the range of core promoter elements interacting with the pol II transcriptional machinery.…”
Section: Discussionmentioning
confidence: 98%
“…This sequence, conserved ϳ30 bp downstream from the RNA start site in a variety of Drosophila TATA-less promoters, greatly enhances the activity of upstream Inr modules (12)(13)(14)(15)(16)(17). DPE interacts with specific components of the Drosophila TFIID complex (dTAFII40 and dTAFII60; see Ref.…”
mentioning
confidence: 99%
“…Previous studies showed that $40 bp located at the 5 H ends of complete Drosophila I, F and Doc LINE elements contain all the information necessary to direct basal transcription (Minchiotti & Di Nocera, 1991;Contursi et al, 1993Contursi et al, , 1995Mc Lean et al, 1993). These DNA intervals can be viewed primarily as two regions, A and B ( Figure 1A).…”
Section: Modular Structure Of Doc F and I Promotersmentioning
confidence: 97%
“…LINEs are mobile DNA sequences conserved in evolution from protozoa to man (Singer & Skowronski, 1985; which use self-encoded proteins to reverse transcribe their own mRNA and integrate cDNA copies at new genomic locations (Pelisson et al, 1991). LINEs lack long terminal repeats (LTRs), and their transcription is regulated by cis-acting signals located at and downstream from the RNA start site(s) Mizrokhi & Mazo, 1990;Swergold, 1990;Minchiotti & Di Nocera, 1991;Minakami et al, 1992;Becker et al, 1993;Contursi et al, 1993Contursi et al, , 1995McLean et al, 1993). Whereas many eukaryotic species contain a single LINE family, eight distinct LINE families coexist in Drosophila melanogaster: the I factor (Fawcett et al, 1986), F (Di Nocera & Casari, 1987), G (Di Nocera, 1988 jockey (Priimagi et al, 1988), Doc (Driver et al, 1989) and BS (Udomkit et al, 1995) elements, and type I and type II ribosomal DNA insertions (Jacubczak et al, 1990).…”
Section: Introductionmentioning
confidence: 99%